Revisiting prompting in the age of digital pedagogy: a theoretical analysis of pedagogical techniques in contemporary educational technologies - Rad, Dana; Roman, Alina; Marcu, Radiana; Bennett, Ramona Tatiana (Technium Social Sciences Journal, 2024)
This research revisits the utilization of prompting as an essential teaching technique in digital pedagogy, taking into account its changing significance in response to technological progress. This study presents a paradigm that highlights the importance of prompting in supporting digital learning environments. It analyzes different types of prompting, their usefulness, and how learning progresses through strategies like fading and shadowing. Additionally, this study examines the practical consequences, implementation processes, and future research issues in the field of digital pedagogy.